THE ROLE OF VISIBLE LIGHT IN OPTIMIZING HYDROGEN YIELD DURING ALKALINE ELECTROLYSIS - Santoso, Mardi; Ahmad, Anton Royanto; Purnami, Purnami; Hamidi, Nurkholis (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Hydrogen is a clean energy carrier, but the efficiency of its production via alkaline water electrolysis remains a key challenge due to high energy consumption and limited reaction kinetics. This study explores the potential of visible light irradiation—specifically red, green, and blue LEDs—to enhance hydrogen production efficiency under standard electrolysis conditions. Using NiFe electrodes in 30% KOH solution, experiments were conducted at 9 V and 1.5 A for 10 minutes, with each LED source (700 lumens) positioned 50 mm above the electrolyte. Hydrogen yield was recorded via a water displacement method, and temperature changes were monitored to assess photothermal effects. Results showed a significant improvement in hydrogen production under light exposure, with blue light yielding the highest output (17.85 mL), followed by green (13.15 mL), red (10.65 mL), and the non-irradiated control (8.15 mL). These enhancements are attributed to the synergistic effects of photon energy and thermal stimulation, which improve electrochemical kinetics. This study provides evidence that visible light can be an effective, low-cost method to boost hydrogen evolution performance in alkaline electrolysis systems.